Peningkatan hasil belajar alat indra manusia melalui pendekatan Saintifik - Yunita Laila Zulfa; Dahlia Dahlia (Liberi, 2024)
The aim of this exploration is to enhance the learning achievement in science regarding human sensory organs by utilizing the scientific method within the environment of grade IV MI classroom. This exploration aims to investigate whether the implementation of the scientific method can elevate the learning achievement capabilities of students in grade IV MI. The experiment is conducted in the grade IV MI classroom. The entire experiment is divided into two cycles, running from April to May 2024. The research population consists of 25 fourth- grade students, comprising 8 male students and 17 female students. The data collection approach in the experiment involves test techniques, observation, and documentation. The exploration results conclude that the learning achievement of students regarding human sensory organs in grade IV MI in the initial cycle still demonstrates satisfactory achievement, with an average score of 78.6. Sixteen out of 25 students, or 64%, successfully achieve the expected level of individual achievement. Meanwhile, in the subsequent cycle, there is a significant improvement with very good achievement, averaging 91, and twenty-two out of 25 students, or 88%, successfully achieve the expected level of individual achievement. Thus, the conclusion drawn is that the implementation of the scientific approach is capable of enhancing the learning achievement in science regarding human sensory organs in the environment of grade IV MI classroom.